The Road to TNR: Examining Trap-Neuter-Return Through the Lens of Our Evolving Ethics - Wolf, Peter Joseph; Schaffner, Joan E. (Frontiers in Veterinary Science, 2019)
In the 2008 article “A Review of Feral Cat Control,” Robertson explored the trend developing in the management of so-called “feral” cats away from lethal methods toward the non-lethal method of trap-neuter-return (TNR). The review explored various issues raised by the presence of these unowned, free-roaming cats in our neighborhoods (e.g., zoonotic disease and wildlife predation), stakeholder interests, and management options—all based on then-available information. Missing from the review, however, was an exploration of the shifting ethics underlying TNR’s increasing popularity. In this essay, we explore the ethical aspects of community cat management in the U.S. as reflected in the momentum of the “no-kill movement” generally and TNR in particular. We argue that these powerful cultural currents reflect two interrelated ethical theories: (1) a zoocentric ethic that recognizes the intrinsic value of non-human animals beyond any instrumental value to humans, and (2) a virtue ethic that recognizes the legitimacy of “emotional” considerations (e.g., compassion) that rightly accompany decisions about how best to manage community cats.